Pengaruh tinggi tempat terhadap tingkat serangan hama penggerek buah kakao (Conopomorpha cramerella Snellan) di Kabupaten Pidie - Syarkawi Syarkawi; Husni Husni; Muhammad Sayuthi (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
Effect of the Altitude on the Level of Cocoa Pod Borer (Conopomorpha Cramerella Snellen) Attack in Pidie DistrictABSTRACT. This study aims to look at the effect of altitude on the level of pest infestation C. cramerella, so getting information as a data source control of pests C. cramerella future. This study was conducted in garden cocoa folk in Pidie district, starting from January to March 2015. This study used survey method. Factors examined in this study was the effect of altitude on the level of C. cramerella attack, carried out with purposive sampling method. Altitude is divided into four categories (A = 0-200 m dpl, B = 201-400 m dpl, C = 401-600 m dpl, dan D = 601-800 m dpl). Altitude affects the level of attacks pests C. cramerella, the highest attack at the location A to 76.77%, and attacks decreased in the location D is 31%. PBK altitude affects the population, the highest population found in the location A with an average 328.60 compared to the location D is only 95.80. There is a positive correlation between the temperature with an attack percentage of fruit and pests C. cramerella population, but the humidity showed a negative correlation to the percentage of fruit attacks and pests C. cramerella populations.